Application of mathematical simulation of X-ray radiography procedure to development of diagnostic reference levels - Minenko, Victor; Viarenich, Kiryl (Journal of the Belarusian State University. Ecology, 2023)
Entrance surface dose at patient skin during X-ray radiography was studied. This quantity is used for determination of diagnostic reference levels (DRLs). These levels are the main tool for optimisation of radiation protection of patients. Objective: show the possibility of computer simulation of diagnostic exposure for determination of DRLs for standard chest X-ray in anteroposterior projection. Materials and methods: X-ray spectrum was calculated using «SpekPy» computer software; X-ray transport was simulated using Monte-Carlo method and voxel anthropomorphic phantom. Focal sport of the X-ray tube was modelled with point source. Rectangular field of the radiation beam was formed by lead curtains. esults: entrance surface dose on the patient’s skin, backscatter factor and dose on the surface of image receptor were calculated for various combinations of exposure parameters (X-ray tube voltage, focus-surface distance, field size). Linear dependence of entrance surface dose and X-ray tube output on square of X-ray tube anode voltage was found. The dependence, which we found, allows calculation of these quantities for anode voltage different from the value at which the X-ray tube output was measured. Optimal radiation parameters were found, under which the entrance surface dose would not be exceeded. It was also found that entrance surface doses do not have strong dependence on the radiation field size for chest X-ray. Conclusion: optimal settings of exposure can be made based on diagnostic reference levels before the exposure. It can be facilitated by using a computer program with a database of entrance surface dose values, which were calculated using computer simulation in advance. Entrance surface dose can be calculated based on backscatter factor and measurements of X-ray tube output.